The Moderating Influence of Inherent Project Risk on the Relationship between Project Planning and Perceived Project Success - Arthur Ahimbisibwe; Wilson Tusiime; Ronald Tumuhairwe (International Journal of Supply Chain Management, 2015)
Project planning is considered to be a critical success factor for project success. However, recent literature questions whether planning has similar importance in various project contexts. This research investigates the effectiveness of project planning on project success in various project risk contexts of software development projects. A survey based research design was used to collect data to test the proposed model. The results reveal that various inherent project risks can moderate the effects of project planning on project success and in different ways for various success measures. More specifically, the results indicate that project planning makes a greater contribution to project success when there is a low level of inherent project risk and its positive impact on project success diminishes when there is a high level of inherent project risk. The results of this study contribute to a more acute understanding of the contingency approach to software project risk management. Practical implications of these results suggest that project managers should put more emphasis on less detailed formal planning in high risk project situations in order to meet project success.